Wide Field of View Head Mounted Display for Tele-presence with An Omnidirectional Image Sensor - Nagahara, Hajime; Yagi, Yasushi; Yachida, Masahiko (2003 Conference on Computer Vision and Pattern Recognition Workshop, 2003)
Recently, the omnidirectional image sensors have been applied to tele-presence systems, because the sensor can capture images with large field of views at video rate. On the other hand, head mount display (HMD) has been generally used as a personal display for virtual reality applications such as a tele-presence. However, almost all HMDs have a problem that the field of view (FOV), about 60 degree horizontally, of its presented image was terribly narrower than that of human. The problem makes reality and immersion lower in these applications. In this paper, we propose high-immersive visualization system that can display 180 degrees horizontal view by using a new catadioptrical HMD and an omnidirectional image sensor. The HMD consists of ellipsoidal and hyperboloidal curved mirrors, and can display 180 degrees horizontal view.